Reconstruction of medium-size defects of the oral cavity: radial forearm free flap vs facial artery musculo-mucosal flap - Badr Ibrahim; Akram Rahal; Eric Bissada; Apostolos Christopoulos; Louis Guertin; Tareck Ayad (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The radial forearm free flap (RFFF) is the most commonly used flap for defects of the oral cavity. The facial artery musculomucosal (FAMM) is a safe and effective method to reconstruct medium sized defects of the oral cavity. No comparison exists between the FAMM flap and RFFF. Methods 1) Retrospective chart review from 2007 to 2016. 2) Cost difference analysis. Results Thirteen FAMM flap cases and 18 RFFF met inclusion criteria. The FAMM flap showed a tendency to lower rates of return to the operating room (p = 0.065) as well as lower rates of complications not requiring return to the OR with 1 complication in 1 patient as opposed to 10 patients with 15 complications (p = 0.008). Also, FAMM flap had shorter operative times compared to the RFFF group (7.2HR and 8.9 HR respectively, p = 0.002). The average operative room related costs for a FAMM flap were 6510 CAD vs 10,703 CAD for RFFF (p < 0.0005). Speech and swallowing outcomes were similar (p > 0.05). Conclusion The FAMM flap can be used for reconstruction of medium-size defects of the oral cavity with functional outcomes similar to the RFFF while decreasing the associated costs and morbidity. Graphical Abstract